Rhetorical Analysis of Women’s Status and Social Injustice in Taslima Nasrin’s Speech and Interview - Paudyal, Ganga Ram (Janapriya Journal of Interdisciplinary Studies, 2022)
This paper explores Taslima Nasrin in terms of the issues related to women’s status, freedom of expression, secularism, and religious fanaticism, using her speeches and interviews. She opposes ritual practices of Islam in particular and all religions in general, which limit women’s rights and freedom of expression. She herself has become the victim of the subjugation due to her revolutionary ideas for the empowerment of women. Therefore, the objective of this paper is to find how women are marginalized in multiple ways by religious practices that have created problems in societies, making a division among the fanatical people. She shows how religion and patriarchy have been trying to dominate women without advocating for freedom and equality. Secularism and dogmatic ideas have caused the segregation of women. Her emphasis is on the reformation of those narrow concepts. Based on her interviews and speeches, rhetorical analysis is made regarding the status of women in Islamic countries and religious fundamentalism. This paper applies descriptive method to make analysis of her speeches and interviews which are the primary source of the concepts. The finding refers to take collective effort for the liberation and empowerment of women. Speeches and writings can best be used to persuade people for the status of women and reformation in the society.